Supercooling of Silver Nano Composite PCM Microcapsules (Journal of Fiber Bioengineering and Informatics, 2008)
Supercooling effects of novel Phase Change Materials microcapsules incorporated with silvernano particles (NC-MicroPCMs) and conventional PCM microcapsules (MicroPCMs) are compared andevaluated systematically. Melting and crystallization behaviors of microcapsules with different processingparameters are investigated mainly by DSC measurements. Combinations of processing parameters aredetermined by a full factorial experimental design. The influences of processing parameters are discussedand analyzed by statistical softwares of SPSS and Minitab. The results have shown that the formation ofnano composite structure can reduce the effect of supercooling. The possible mechanisms have also beenexplored.